Pengaruh Game Wordwall Match Up dan Wordsearch terhadap Kognitif Siswa SD Laboratorium Percontohan UPI Serang - Nurul Safira; Annisa Rizky Amalia; Sistya Fhirdhan Anjani; Eneng Mufadillah; Mega Andini Putri; Muhammad Hanif (SAP (Susunan Artikel Pendidikan), 2023)
This study aims at finding out how interactive Wordwall is in order to evaluate learning in improving students' cognitive. This data was obtained from 13 students of grade 4 of UPI Serang Pilot Laboratory. This study employed a mixed method. The results of the analysis were carried out through written test activities, Match Up games and Wordsearch games. This research was conducted by an experiment. Students carried out an evaluation with a written test first and then continued using the Wordwall Match Up game, students were asked to pair pictures with the correct statements and Wordsearch, students were asked to look for words about picture tools. The problems of the written test and Wordwall were different but still on the same level. Based on the results of the study, it discovers that Wordwall is one of the interesting media in evaluating learning and it is able to improve students' cognitive.